Association of Maternal BMI with Obstetric and Perinatal Outcomes: Maternal Body Mass Index with Obstetric and Perinatal Outcomes - Bibi, Shabana; Sajjad, Rabia; Uzma, Syeda; Chaudhary, Sadia Zainab; Iqbal, Attiya; Hayat, Naheed (Pakistan Journal of Health Sciences, 2025)
The increasing prevalence of obesity among women of childbearing age is linked to a higher risk of pregnancy complications. Maternal obesity affects both obstetric and perinatal outcomes, posing risks for mother and child. Objective: To investigate the relationship between maternal BMI and obstetric and perinatal outcomes. Methods: A cross-sectional study was conducted at the Department of Obstetrics and Gynecology, Tertiary Care Hospital Bahawalpur, from January to July, 2022. A total of 254 pregnant women were categorized into underweight, normal, overweight, and obese groups based on BMI. Data on Gestational Diabetes Mellitus (GDM), Pregnancy-Induced Hypertension (PIH), and mode of delivery, labor complications, postpartum hemorrhage, preterm labor, and NICU admissions were analyzed using SPSS version 25.0. Results: Higher incidences of GDM (31.9% in obese vs. 10.6% in underweight) and PIH (23.1% in obese vs. 7.7% in underweight) were observed, though not statistically significant (p = 0.088 and p = 0.463, respectively). Obese mothers had more cesarean sections (24.6% vs. 13.8% in underweight, p = 0.178) and increased NICU admissions (18.9% vs. 8.1%, p = 0.788). Conclusions: This study observed clinically relevant trends suggesting that higher maternal BMI may be associated with adverse obstetric and perinatal outcomes, including increased rates of gestational diabetes, hypertension, cesarean sections, and NICU admissions. Although statistical significance was not reached, findings emphasize the importance of maternal weight management in prenatal care.